Differentiation in the process of English language teaching - Baksha Rebeka; Baksa Rebeka; Бакша Ребека; Huszti Ilona; Густі Ілона; Annamaria Kachur; Kacsur Annamária; Качур Аннамаріа (Видавничий дім «Гельветика», 2024)
Abstract. This article explores the intricate complexities and fundamental necessity of differentiation in language instruction, particularly within the multifaceted context of English as a Foreign Language (EFL) teaching. Acknowledging that learners are far from a homogeneous group, but rather exhibit an impressive spectrum of diverse backgrounds, abilities, and motivations, the study critically examines the conventional educational model that imposes uniformity while neglecting individual learner differences. The concept of a "general learner" is argued to be a misleading fallacy that inadequately addresses the unique and varied needs of each student. The article underscores the importance of innovative, tailored teaching strategies that are responsive to these differences, thereby enabling learners to progress at their own pace and according to their learning styles. Through an extensive review of the existing literature, the study examines the pivotal role of differentiation as an essential approach in language teaching. It highlights how differentiation can enhance motivation, critical thinking, and overall language proficiency among students. The article deals with various influential factors – such as age, gender, personality traits, and learning styles-that significantly impact language learning outcomes. The authors advocate for a paradigm shift in EFL instruction, emphasizing the critical need for educators to adopt highly flexible and adaptive teaching methods. This shift necessitates the thoughtful modification of lesson plans, the creative employment of a wide range of teaching activities, and the deliberate fostering of an inclusive and supportive learning environment. Ultimately, the authors earnestly call for ongoing, reflective dialogue among educators to share valuable experiences and progressively refine pedagogical practices, thereby ensuring that the diverse and complex needs of all learners are adequately met in increasingly varied and dynamic classrooms.

Резюме. Стаття досліджує складні аспекти та фундаментальну необхідність диференціації в мовній освіті, зокрема в багатогранному контексті викладання англійської як іноземної мови (IM). Визнаючи, що учні далекі від однорідної групи, а навпаки, демонструють вражаючий спектр різноманітного досвіду, здібностей та мотивацій, дослідження критично аналізує традиційну освітню модель, яка нав’язує уніфікацію, нехтуючи індивідуальними відмінностями учнів. Концепція «загального учня» розглядається як оманлива ілюзія, яка недостатньо враховує унікальні та різноманітні потреби кожного студента. Стаття підкреслює важливість інноваційних, адаптованих викладацьких стратегій, що реагують на ці відмінності, дозволяючи учням просуватися у власному темпі та відповідно до їх стилів навчання. Завдяки розширеному огляду наукової літератури, наше дослідження вивчає ключову роль диференціації як необхідного підходу в мовній освіті. Воно підкреслює, що диференціація може суттєво підвищити мотивацію, критичне мислення та загальну мовну компетентність учнів. Стаття розглядає різні впливові фактори, такі як вік, стать, риси особистості та стилі навчання, які значно впливають на результати навчання ІМ. Автори закликають до зміни парадигми в навчанні ІМ, наголошуючи на критичній необхідності для викладачів приймати адаптивні методи навчання. Ця зміна вимагає продуманих модифікацій навчальних планів, креативного використання широкого спектру навчальних заходів і цілеспрямованого сприяння інклюзивному та підтримуючому навчальному середовищу. Зрештою, автори щиро закликають до постійного, рефлексивного діалогу серед викладачів для обміну цінним досвідом та поступового вдосконалення педагогічних практик, що, у свою чергу, забезпечує адекватне задоволення різноманітних та складних потреб усіх учнів у дедалі більш різноманітних та динамічних класах.
Диференціація в процесі навчання англійської мови
Редакційна колегія: https://chasopys.ps.npu.kiev.ua/redcolegiya
Зміст: https://chasopys.ps.npu.kiev.ua/nc-100
Keywords: differentiation; differentiated instruction; English as a foreign language teaching; heterogeneous classroom; individual learner variables; learner differences; method of differentiating; motivation; відмінності серед учнів; диференціація; диференційоване навчання; індивідуальні відмінності учнів; методи диференціації; навчання англійської мови як іноземної; неоднорідний клас; стилі та стратегії навчання